The Effectiveness Test of Ultrasonic Extraction Microwave Distillation (USE-MD) Method in Capsaicin Extraction - Ach. Ferdiansyah Pradana P; Moch. Dimas Khoirul U; Angga Septian E (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2017)
Chili (Capsicum frutescens) is one of foodstuffs whose price is fluctuate and still not processed well, so it becomes damaged. Processing chili becomes capsaicin extract can be done by using MAE method that requires high power and UAE method that produces low yield. Therefore, this study aimed to process chilies as capsaicin extract by using USE-MD and ME-MD methods. Chilies were extracted using 500 ml ethanol 96% in 10, 20, 30, 40 and 50 minutes. The operating condition of the distillation was 78oC with a pressure of 1 atm. The result showed that the best method to get capcaisin extract was USE-MD method with optimum extraction time about 30 minutes. This method gave yield about 2.795% with concentration of capsaicin about 0.94 + 0.02% lb/lb